2021
DOI: 10.1021/acs.iecr.1c01832
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Light Aromatics and Coke during Catalytic Reforming of Biopolymer-Derived Volatiles over HZSM-5

Abstract: In this study, the formation mechanism of light aromatics including benzene, toluene, ethylbenzene, xylene, and naphthalene (BTEXN) and the coke growth during catalytic reforming of thermally derived volatiles of cellulose, glucose, and lignin over HZSM-5 under a H 2 atmosphere were investigated rigorously. The shape selectivity of HZSM-5 coupled with H 2 as the promoted agent was found to be highly efficient in trapping volatiles to promote the production of BTEXN. The reactivity of the three biopolymers from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 70 publications
0
15
0
Order By: Relevance
“…The gas yield and C dep were 22.3 mmol/g and 22.3%, which can be explained as the serious carbon deposition. As reported in the literature, tar can be easily adsorbed over the acidic support and then generated coke especially the Ni/Z catalyst with a high Si/Al ratio . Carbon deposition over spent Ni/Z catalysts was analyzed by TPO-MS (Figure d).…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…The gas yield and C dep were 22.3 mmol/g and 22.3%, which can be explained as the serious carbon deposition. As reported in the literature, tar can be easily adsorbed over the acidic support and then generated coke especially the Ni/Z catalyst with a high Si/Al ratio . Carbon deposition over spent Ni/Z catalysts was analyzed by TPO-MS (Figure d).…”
Section: Resultsmentioning
confidence: 88%
“…As reported in the literature, tar can be easily adsorbed over the acidic support and then generated coke especially the Ni/Z catalyst with a high Si/Al ratio. 48 Carbon deposition over spent Ni/Z catalysts was analyzed by TPO-MS (Figure 7d). On the basis of the results, it was found that Ni/Z5 with worse activity exhibited the worst coke resistance in CTR, and 44.7 mg coke /g cat.…”
Section: Rd (%)mentioning
confidence: 99%
“…However, its rapid deactivation caused by coke deposition is still a big challenge for application . The diffusional limitation of micropores for macromolecular oxygenates and the excessive acid sites on the surface are the main reasons for deactivation. Hierarchical Z5 zeolite has shown great potential to improve the mass transfer efficiency during the CFP of biomass, while it inevitably suffers from heavy coke formation caused by the on-surface strong acid sites. Thus, it is necessary to improve the catalytic performance by regulating the surface acid sites of the hierarchical Z5 catalyst through metal modification.…”
Section: Introductionmentioning
confidence: 99%
“…Aromatization is the main pathway for small-molecule oxygenates and olefins to form aromatics through the “hydrocarbon pool mechanism,” activated by the shape-selective effect of ZSM-5 zeolite channels. 16 …”
Section: Introductionmentioning
confidence: 99%
“…With the shortage of fossil resources and increasing carbon emissions, biomass energy, as the only renewable carbon source, has gradually attracted attention to replace traditional fossil resources. Catalytic fast pyrolysis (CFP) is a promising technology for producing aromatics directly from biomass that integrates fast pyrolysis and catalytic cracking technology. , In recent years, extensive research into the reaction mechanism and catalysts for CFP has been reported. Aromatization is the main pathway for small-molecule oxygenates and olefins to form aromatics through the “hydrocarbon pool mechanism,” activated by the shape-selective effect of ZSM-5 zeolite channels …”
Section: Introductionmentioning
confidence: 99%